2019
DOI: 10.1038/s41388-019-0961-9
|View full text |Cite
|
Sign up to set email alerts
|

The dysfunction of BP180/collagen XVII in keratinocytes promotes melanoma progression

Abstract: The current affiliation of Zhen Liu is the Guangdong Center for Adverse Drug Reactions of Monitoring, Guangzhou, PRC. The current affiliation of Maureen Su is, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…In vivo models using skin specific-NC16A dysfunctional mice with B16 melanoma cells support the regulatory role of keratinocyte collagen XVII on melanoma tumorigenesis (61,62). When compared to the controls, the experimental models showed increased levels of tumor volume and lymphatic metastasis (62).…”
Section: Neural Crest Tumorsmentioning
confidence: 76%
See 3 more Smart Citations
“…In vivo models using skin specific-NC16A dysfunctional mice with B16 melanoma cells support the regulatory role of keratinocyte collagen XVII on melanoma tumorigenesis (61,62). When compared to the controls, the experimental models showed increased levels of tumor volume and lymphatic metastasis (62).…”
Section: Neural Crest Tumorsmentioning
confidence: 76%
“…In vivo models using skin specific-NC16A dysfunctional mice with B16 melanoma cells support the regulatory role of keratinocyte collagen XVII on melanoma tumorigenesis (61,62). When compared to the controls, the experimental models showed increased levels of tumor volume and lymphatic metastasis (62). Collagen XVII dysfunction results in immediate inflammation, previously identified as a hallmark for cancer, through the influx of chemokines which further recruit myeloid derived suppressor cells (MDSCs) (61,63).…”
Section: Neural Crest Tumorsmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, basal keratinocytes express BP180/collagen XVII, which is a cell-matrix adhesion protein related to different types of skin cancers, including melanoma [ 48 , 49 ]. Hwang et al showed that keratinocytes derived from BP180-deficient mice exhibited the upregulation of CXCL1 expression compared to control animals, in which cytokine acts as a chemoattractant for myeloid-derived suppressor cells (MDSCs).…”
Section: Keratinocytesmentioning
confidence: 99%